2015
DOI: 10.9734/bbj/2015/13145
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Phenotypic Identification of Vancomycin-Resistant Staphylococcus aureus Isolates from Retail Poultry Carcasses in Omu-Aran, North-Central Nigeria

Abstract: Staphylococcus aureus is a well-known agent of zoonotic infections. Livestock-associated methicillin-resistant S. aureus (LA-MRSA) had been receiving public health attention for over a decade. Recently, the genomes of some MRSA strains evolved further by enabling acquisition of vanA gene from enterococcus which drives the emergence of vancomycin-resistant S. aureus (VRSA), thus signaling a higher threat to antimicrobial chemotherapy and diagnostic microbiology. This study was designed to examine slaughtered ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…These findings agree with those of Kapllan et Tiwari and Sen (2006), who reported that vancomycin resistance isolates could be detected phenotypically while not carrying vanA and vanB genes. Several reports showed various levels of correlation between gene detection and agar-based identification of staphylococcal vancomycin-resistant phenotype (Okolie et al, 2015). Failure of PCR to detect the genes encoding vancomycin resistance could be multifactorial, ranging from poor primer to the absence of the target gene (or sequence) within the genome.…”
Section: Discussionmentioning
confidence: 99%
“…These findings agree with those of Kapllan et Tiwari and Sen (2006), who reported that vancomycin resistance isolates could be detected phenotypically while not carrying vanA and vanB genes. Several reports showed various levels of correlation between gene detection and agar-based identification of staphylococcal vancomycin-resistant phenotype (Okolie et al, 2015). Failure of PCR to detect the genes encoding vancomycin resistance could be multifactorial, ranging from poor primer to the absence of the target gene (or sequence) within the genome.…”
Section: Discussionmentioning
confidence: 99%
“…6). Martins et al (2013) detected vanA gene in 3 samples out of 15 of chilled industrialized uncooked chicken parts and Okolie et al(2015) found vanA in 22 isolates out of 155 from chicken carcasses. On other hand, Saadat et al (2014) detected van A in 34% of clinical isolates in hospital, while Khudaier(2018) detected van A in 4 human isolates out of 163 (2.5%).…”
Section: Discussionmentioning
confidence: 99%